A REVIEW: MICROPROPAGATION OF PHALAENOPSIS sp FROM LEAF AND FLOWER STALK EXPLANTS - Meutia Zahara (Universitas Syiah Kuala, 2017)
Abstract Phalaenopsis orchids are recognized as the most popular orchid genus in the world, especially in horticultural industry due to their large, colorful, and durable flowers as well as their wider adaptability to room conditions. The characteristics of seedling propagated by vegetative means are not uniform; therefore, propagation through tissue culture is desirable. Although the micro propagation of Phalaenopsis has shown very good development, but the wide spread of micro propagation still limited due some problems such as the exudation of phenolic compounds, the PGR concentration, the media used, somaclonal variation, the chosen explants, etc. This paper endeavor to include some important investigations based on the common explants used; leaf and flower stalk. Keywords: Micropropagation, Phalaenopsis, leaf explant, flower stalk ReferencesAnonymous. Orchid (Orchidaceae). Diakes tanggal 13 Januari 2013 dari http://www.rainforest-alliance.org/kids/species-profiles/orchid. Rainforest Alliance. 2002.Pillon, Y.; Chase, M. W.Taxonomic exaggeration and its effects on orchid conservation. Conservation Biology. 2007, 21, 263–265.Thengane, S. R.; Deodhar, S. R.; Bhosle, S. V.; Rawal, S. K. Direct somatic embryogenesis and plant regenaration in Garciniaindica Chois’. Current Science. 2006, 91(8), 1074-1078.Yuswanti, H.; Dharma, I. P.; Utama. ; Wiraatmaja, I. W. Mikropropagasi anggrek Phalaenopsis dengan menggunakan eksplan tangkai bunga. AGROTROP. 2015, 5(2): 161-166.Raynalta, E.; Sukma, D. Pengaruh komposisi media dalam perbanyakan protocorm like bodies, pertumbuhan plantlet, dan aklimatisasi Phalaenopsis amabilis. J. Hort. Indonesia. 2013, 4(3): 131-139.Kosir, P.; Skof, S.; Luthar, Z. Direct Shoot Regeneration from Nodes of Phalaenopsis of Orchids. Acta Agriculturae Slovenica. 2004, 83, 233–242.Arditti, J. R. ; Ernst. Micropropagation of Orchids. Wiley-Interscience. New York, 1993.Park, Y. S.;Kakuta, S.; Kano, A.; Okabe, M.Efficient propagation of protocorm-like bodies of Phalaenopsis in liquid medium. Plant Cell, Tissue and Organ Culture. 1996, 45, 79–85.Park, S. Y. ; Yeung, E. C.; Chakrabarty, D. ; Paek, K. Y. An efficient direct induction of protocorm-like bodies from leaf subepidermal cells of Doritaenopsis hybrid using thin-section culture. Plant Cell Reports. 2002, 21, 46–51.Zahara, M.; Datta, A.; Boonkorkaew, P. Effects of sucrose, carrot juice and culture media on growth and net CO2 exchange rate in Phalaenopsis hybrid ‘Pink’. ScientiaHorticulturae. 2016,205, 17–24.Hee, K. H.; Loh, C. S.; Yeoh, H. H. In vitro flowering and rapid in vitro embryo production in Dendrobium Chao Praya Smile (Orchidaceae). Plant Cell Reports. 2007, 26, 2055–2062.Kannan, N. An in vitro study on micropropagation of Cymbidium orchids. Current Biotica. 2009, 3, 244–250.Steward, Jr. N. C. Plant Biotechnology and Genetics. Willey, A john Willey Sons, INC., Publication. 2008.George, E. F.; Sherington, P. D.Biotechnology by tissue culture. Exegetics Ltd. 1994.Nursyamsi. Teknik kultur jaringan sebagai alternatif perbanyakan tanaman untuk mendukung rehabilitasi lahan. Makalah pada ekspose hasil-hasil penelitian balai penelitian kehutanan makasar. Makasar, 2010.Aditi, J. F. L. S.; Krikorian, A. D. Orchid mircropropagation: the path from laboratory to commercialization and an account of several unappreciated investigators. Botanical Journal of of the Linnean Society. 1996, 122: 183-241.Gunawan, L. W. Teknik Kultur Jaringan Tanaman. Pusat Antar Universitas (PAU) Bioteknologi IPB. 1998. Bogor.Chugh, S. Guha, S.; Rao, I. U. Micropropagation of orchids: A review on the potential of different explants. Scientia Horticulturae. 2009, 122, 507–520.Ramdan. Kultur daun dan pangkal batang in vitro anggrek bulan raksasa (Phalaenopsis gigantea J.J.Smith) pada beberapa media kultur jaringan. Departemen agronomi dan hortikultura, Fakultas pertanian IPB. 2011.Latip, M. A. R.; Murdad, Z. A.; Aziz, L. H.; Ting, L. M.; Govindasamy.; R. Pipin. Effects of N6-Benzyladenine and Thidiazuron on Poliferation of Phalaenopsis gigantea Protocorm. AsPac J. Mol. Biol. Biotechnol. 2010, 18(1): 217-220 p.Niknejad, A.; Kadir, M. A.; Kadzimin, B. S. In vitro plant regeneration from protocorms-like bodies (PLBs) and callus of Phalaenopsis gigantea (Epidendroidaceae: Orchidaceae). African Journal of Biotechnology.2010, 10, 11808–11816.Chen, J. T.; Chang, W. C. Direct somatic embryogenesis and plant regeneration from leaf explants of Phalaenopsis amabilis. Biologia Plantarum. 2006, 50, 169–173.Zahara, M. Disertasi doktor: The Effects of Plant Growth Regulators and Natural Additives on Direct Shoot Regeneration and Plantlet Growth of Phalaenopsis hybrid ‘Pink’. Asian Institute of Technology, Pathumthani. Thailand. 2016.Xu, C. J.; Li, H.; Zhang, M. G. Preliminary studies on the elements of browning and the changes in cellular texture of leaf explant browning in Phalaenopsis. Acta Horticulturae Sinica. 2005, 32, 1111–1113.Tokuhara, K; Mii, M. Induction of embryonic callus and cell suspension culture from shoot tips excised from flower stalk buds of Phalaenopsis (Orchidaceae). In Vitro Cellular Developmental Biology–Plant. 2001, 37, 457–461Balilashaki, K.; Naderi, R.; Kalantari, S.; Soorni, A. Mircropropagation of Phalaenopsis amabilis cv Cool ‘Breeze’ with using flower stakl nodes and leaves of sterile obtained from node cultures. IJFAS, 2014.Semiarti, E.; Indrianto, A.; Purwanto, A. Agrobacterium-Mediated transformation of Indonesian orchids for micropropagation, genetic transformation, Prof. MarÃa Alvarez (Ed.), ISBN: 978-953-307-364-4, InTech, 2011. Available from: http://www.intechopen.com/books/ genetic-transformation/agrobacterium-mediated-transformation-ofindonesian-orchids-for-micropropagation.